A novel approach to improve mechanical properties of parts fabricated by fused deposition modeling. (5th September 2016) - Wang, Jianlei; Xie, Hongmei; Weng, Zixiang; Senthil, T.; Wu, Lixin
Abstract: The mechanical properties of fabricated parts by fused deposition modeling (FDM) are impaired by significant voids between deposition lines. In this study, a novel approach that adding thermally expandable microspheres into matrix and combining FDM process with thermal treatment was proposed to tackle the problem. The influences of microsphere content, heating temperature and heating time were investigated. The results show that appropriate conditions of thermal treatment exert a positive influence on mechanical properties. With the addition of 2 wt.% microspheres, tensile and compressive strength of samples heated at 140 °C for 120 s increase 25.4% and 52.2%, compared to untreated samples, respectively. A new process is developed to prepare foam materials based on FDM, which will have the potential applications in shoes industry. Graphical abstract: Highlights: Thermally expandable microspheres were added to diminish voids between deposition lines. The effects of microsphere content, heating time and heating temperature on mechanical properties were investigated. The appropriate conditions of thermal treatment exerted a positive influence on mechanical properties. A new process was developed to prepare foam materials based on fused deposition modeling.